NUMERICAL STUDY OF THE EFFECTS OF EVAPORATIVE COOLER SUPPLY AIR OUTLET HEIGHT ON THERMAL COMFORT - IBRAHIM USMAN HARUNA; IBRAHIM AHMAD RUFAI; BALARABE YAHAYA (Journal of Engineering Studies and Research)
Thermal comfort in a space equipped with a direct evaporative cooler is a function of the height of the cooler's supply air outlet. This article attempts to numerically investigate the impact of hybrid downdraft evaporative cooler (HDEC) supply outlet height on occupant thermal comfort in an office building. DesignBuilder CFD parametric simulations was carried out by varying the height of the HDEC supply outlet from 0.1m to 2.4 m, step 0.1 m above ground level, using Predictive Mean Vote (PMV) as an objective function. The results show that the best PMV of -0.27 was obtained at 0.4m above the floor level.